CUSTOMER LOYALTY FROM PERSPECTIVE OF MARKETING MIX STRATEGY AND CUSTOMER SATISFACTION A study from Grab - Online Transportation in Era of Industrial Revolution 4.0 - Ade Permata Surya (MIX: Jurnal Ilmiah Manajemen, 2019)
ABSTRACT. This study aims to examine and analyze the influence of marketing mix 7P (product, price, promotion, place, people, physical evidence, and process) on costumer loyalty with the mediating role of customer satisfaction. A lesson from case of overlapping online transportation user base in Indonesia, specificly from Grab’s Consumer perspective. The research was design by using conclusive experiment, in casual type, with quantitative and survey methods. The sampling method used is sampling judgmental and the data was analized by SEM-PLS with WarpPLS 6.0. Data was taken by giving questionaire to 406 respondents. Respondents are Grab’s consumer. The result shows that the variable such as price, promotion, place, people, and process were significantly positif give effect to customer satisfaction, and customer satisfaction affected customer loyalty positifly and significantly.  In other hand, product and physical evidence were not significantly give effect. Adjusted R-squared coefficients of customer satisfaction and customer loyalty were 0,540 and 0,512 which means 54% of customer satisafction can be made by marketing mix variables and 51,2% of customer loyalty can be made by customer satisfaction. The future research in the same topic can use probability sampling method, especially stratified random sampling, and researcher can compare to another ASEAN countries’ data to enhance the more meaningful insight.